Sleepless : unleashing the subversive power of the night self - Abbs, Annabel (G. P. Putnam's Sons, 2024)
"In the winter of 2020, Annabel Abbs-Streets experienced a series of losses: her stepfather, then father, and finally her family's puppy. Unmoored by grief, she couldn't sleep. But she discovered something surprising: during her wakeful nights, the darkness became a place of sanctuary, filled with creativity, reflection, and wonder. And once she stopped fighting her insomnia, Annabel tapped into something mysterious and beguiling: her Night Self. In the tradition of books like Breath and Wintering, Sleepless combines science, historical research, and personal experience to explore the complicated relationship women have with darkness. Her night journeys range from quiet country fields to brightly lit city streets to the darkest reaches of the Arctic Circle. And from women of the past -- Lee Krasner, Virginia Woolf, Louise Bourgeois, and dozens more -- who opened their minds on sleepless nights, to contemporary women who found a form of healing in darkness. From moth hunters to astronomers, from artists to photographers, Annabel found she wasn't alone. Cut loose from the anxiety of insomnia, numerous women discovered strength, imagination, and inner knowledge at night. Many also learned to-finally-sleep"--